2002
DOI: 10.1002/1615-9861(200208)2:8<1007::aid-prot1007>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic approach to identify developmentally regulated proteins in Leishmania infantum

Abstract: We used comparative two-dimensional gel electrophoresis (2-DE) and mass spectrometry methodologies to highlight and identify proteins that are differentially expressed in the intracellular stage of the parasite Leishmania donovani infantum, a causative agent of visceral leishmaniasis. During its digenetic life cycle, Leishmania alternates between the alimentary tract of the sandfly vector as an extracellular promastigote and the acidic phagolysosomes of macrophage cells as an intracellular amastigote. Proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 67 publications
2
62
0
2
Order By: Relevance
“…Promastigotes were cultured at pH 7.0 and 25°C in SDM-79 medium supplemented with 10% heatinactivated fetal calf serum (Multicell, Wisent Inc.) and 5 g/ml hemin. L. infantum promastigote to amastigote differentiation in a host-free culture and the maintenance of axenic amastigotes were performed as previously described (22,27). Briefly, late stationary phase promastigotes (in average 6-day promastigotes) were inoculated in MAA/20 medium in 25-cm 2 -ventilated flasks and grown at 37°C and pH 5.8 with 5% CO 2 for ϳ5 days until they fully differentiated to amastigote-like forms.…”
Section: Cell Lines Leishmania Culture and Macrophage Infections Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Promastigotes were cultured at pH 7.0 and 25°C in SDM-79 medium supplemented with 10% heatinactivated fetal calf serum (Multicell, Wisent Inc.) and 5 g/ml hemin. L. infantum promastigote to amastigote differentiation in a host-free culture and the maintenance of axenic amastigotes were performed as previously described (22,27). Briefly, late stationary phase promastigotes (in average 6-day promastigotes) were inoculated in MAA/20 medium in 25-cm 2 -ventilated flasks and grown at 37°C and pH 5.8 with 5% CO 2 for ϳ5 days until they fully differentiated to amastigote-like forms.…”
Section: Cell Lines Leishmania Culture and Macrophage Infections Inmentioning
confidence: 99%
“…Similar data were obtained with the related parasite Trypanosoma brucei, where only ϳ2% of mRNAs showed more than 2-fold differences in expression (20). However, recent proteomic analyses revealed that ϳ9% of the Leishmania proteins are differentially expressed in the amastigote stage (21,22). 6 This difference between large-scale transcriptomic and proteomic studies further outlines the importance of translational and post-translational control in regulating gene expression in this organism.…”
mentioning
confidence: 99%
“…Even so, proteomics have not revealed evident differential expression between cell stages. Only 5% of proteins are differentially expressed between L. (L.) infantum promastigotes and amastigotes [111]. Around 90% of the L. (L.) mexicana proteome is qualitatively unchanged during the life cycle [108].…”
Section: Transcriptome and Proteomementioning
confidence: 62%
“…Global protein profile analyses have contributed with noteworthy perception on energetic and metabolic requirements of amastigotes. Several hypothetical proteins have been identified by proteomic analysis [111,115] confirming their expression for the first time. Studies have identified several protein isoforms differentially expressed during Leishmania life-cycle through successful enrichment of poorly represented proteins [99,116].…”
Section: Transcriptome and Proteomementioning
confidence: 99%
“…(Paba, et al, 2004, Parodi-Talice, et al, 2004, van Deursen, et al, 2003, Leishmania sp. (Acestor, et al, 2002, Drummelsmith, et al, 2003, El Fakhry, et al, 2002, Nugent, et al, 2004, Thiel and Bruchhaus, 2001, Toxoplasma gondii and Cryptosporidium sp. there have been major inroads made into our understanding of the parasite.…”
Section: Accepted Manuscriptmentioning
confidence: 99%